The Ants (Hymenoptera, Formicidae) of Sri Lanka: a taxonomic research summary and updated checklist - Benoit Guénard (ZooKeys)
Sri Lanka represents an important biodiversity hotspot region of the world. Yet, over the past 170 years, exploration of the ant fauna of Sri Lanka has received sporadic attention. Here we provide a synthesis of the regional taxonomic work carried out to date, as well as a historical overview of myrmecological efforts in Sri Lanka, so that it can serve as a baseline for future ant studies. Thus far, eleven of the seventeen known extant ant subfamilies, 79 genera and 341 valid species and subspecies have been recorded in Sri Lanka. 82 species (24%) of the ant fauna are endemic to the island, while 18 species are considered introduced. Our results also highlight that most information available on Sri Lankan ant distribution is restricted to a few districts and largely confined to the 'wet zone'. It is thus likely that other climatic zones, which have received less sampling and taxonomic efforts, may in the future contribute significantly to new discoveries once properly surveyed.